Attachment styles and the traits of the personality disorders - Gawda, Barbara; Czubak, Katarzyna (Studia Psychologica: Theoria et praxis, 2012)
The literature points that attachment is key mechanism in the development of people. According to the attachment theory, the experience of neglect, abandonment and other early traumas have influence on forming the dysfunctions of emotions and personality pathology. The aim of this article is the verification of the thesis about relation between attachment style and personality disorders. The analysis of results of 155 participants has been conducted (persons in the similar age, similar educational level, similar number of females and males). The diagnosis of personality disorder was based on SCID-II (Structured Clinical Interview for Axis – II), and additionally confirmed by PDQ-4 Hyler Inventory. To examine the attachment style the Plopa’s Attachment Styles Questionnaire and the Revised Experiences in Close Relationships Inventory (ECR-R designed by Fraley et al., 2000), were used. The multiple regression model was used to test whether attachment styles maybe the predictors for personality disorders. The current results partly support the Lyddon and Sherry’ thesis. The main predictor for the relations between attachment and personality disorders is the anxious attachment style.